A rat model of stavudine-induced hyperalgesia - Weber, Juliane (My University, 2009)
Stavudine, a nucleoside reverse transcriptase inhibitor (NRTI) used to treat infection by the human immunodeficiency virus (HIV), causes peripheral neuropathy and pain in HIV-positive patients. The mechanisms of this toxic neuropathy are poorly understood, partly because of a lack of animal models of the disease process. I investigated whether long-term daily oral administration of stavudine affects nociception in Sprague-Dawley rats, and whether changes in nociception are accompanied by a general deterioration in the rats’ conditions, as reflected in activity and appetite. Daily stavudine administration induced mechanical hyperalgesia in rats within three weeks without affecting appetite, growth or physical activity, and this hyperalgesia persisted throughout the six weeks of stavudine administration. I then investigated whether central changes underlie the hyperalgesia caused by stavudine in rats by examining inflammatory cytokine secretion and neuronal death in the spinal cord. Daily stavudine administration caused an increase in cytokine-induced neutrophil chemo-attractant (CINC)-1 concentration in the spinal cord after six weeks, but early development of stavudine-induced hyperalgesia did not depend on increases in spinal concentrations of CINC-1 and interleukin (IL)-6, nor on apoptosis or necrosis of spinal neurones. The neurotoxicity of stavudine is thought to derive from mitochondrial toxicity, which has been linked to increased plasma lactate concentration and decreased plasma adiponectin levels caused by lipodystrophy. Thus, I investigated whether a systemic inflammatory response or metabolic dysregulation accompanied stavudine-induced hypernociception by examining plasma adiponectin, lactate, CINC-1 and IL-6 concentrations in rats administered daily stavudine. Plasma adiponectin, lactate, CINC-1 and IL-6 concentrations were unchanged following three or six weeks of daily stavudine administration. Therefore, I have shown that stavudine-induced hyperalgesia is not dependent on spinal cord plasticity, nor on a systemic inflammatory response or extensive metabolic malfunction. Instead, the hyperalgesia I observed may be caused by the adverse effects of stavudine on peripheral neurone functioning. As stavudine administration to healthy rats had no adverse effects besides inducing hyperalgesia and causing a rise in CINC-1 concentration in the spinal cord after six weeks, my results indicate that many other side effects commonly associated with stavudine treatment in HIV-positive patients may arise through interaction with the underlying HIV infection.